Proposta de intervenção na mediação de mães de crianças com Síndrome de Down - Reis, Luciana Bicalho (2015)
Maternal mediation is an important factor in child development and the standard meditational adopted may be affected by different factors of cognitive or emotional nature. This study evaluated and compared the standard of mediation in mothers of children with Down syndrome, before and after an intervention program on mediation, describing the variables such as stress, anxiety, depression, coping strategies, and beliefs and expectations regarding child development. The sample consisted of nine mothers and their children, 2-5 years (M = 3.9 years). The collection was conducted in stages: in the first were applied sociodemographic questionnaire, Child Behavior Checklist [CBCL 1½ / 5 years] Interview to identify Beliefs and Expectations, Scales Beck anxiety and depression, Inventories of Stress Symptoms for adults Lipp (ISSL) and Coping Assessment Interview. In the second stage, the dyads were videotaped during three free and semi structured situations and evaluated by the Mediated Learning Scale (MLE Rate Scale). In the third stage, with subsample of six participants, it was applied a proposal for intervention in Maternal Mediation, based on MISC - Mediational Intervention for Sensitizing Caregivers with six criteria - Intentionality, Meaning, Transcendence, Behavior Regulation, Praise and Emotional involvement, organized in three workshops. In the fourth stage the dyads were videotaped after intervention at (20 days and 3 months). The data analysis showed that the majority of mothers (n=7) responded to diagnosis with negative feelings, but overcoming them over time. There were predominated (n=8) of positive expectations regarding the development; beliefs around the time of diagnosis, overall had religious character. In the evaluation by the scales Beck and ISSL, three mothers had mild level anxiety and one in moderate level; two with stress resistance phase (prevalence of psychological symptoms). Reported stressors were prejudice/social exclusion, routine appointments, in addition to behavioral problems, development and health of children. In the evaluation of coping strategies, the group predominantly adopted positive adaptive families, Self-confidence (n=8) Support Seeking (n=7), Problem Solving (n=7), Information Seeking (n=7), Accommodation (n=6) and Negotiation (n=1) compared to maladaptive, Avoidance (n=3), Isolation (n=2), Submission (n = 2) and Abandonment (n=1). It was found a significant difference between the means of mediational pattern obtained in the pre-intervention (2.0) and post-intervention (2.5) (Wilcoxon test, p=0,001). Of the six criteria of mediation, five improved in the segment sessions, with transcendence the one which obtained the highest Gain Rate (TG 78%). Mothers presented a good standard of mediation, in association with positive expectations of child development and greater repertoire of adaptive coping strategies of the diagnosis of disability and its stressors. Even so, the intervention helped to improve the quality of mediation between dyads, being thoroughly evaluated by participants. As a result, it is believed that brief and systematized interventions that enable mothers the feeling of competence in their ability as a mediator can help them identify opportunities for mediation of child development, also contributing to the maternal face of disability.